Pengaruh Model Pembelajaran Artikulasi Terhadap Kemampuan Komunikasi Matematis Siswa Kelas XI IPA SMA Negeri 6 Skouw Kota Jayapura - Satrama Royal Hadinata (Journal on Education, 2022)
Mathematical communication is a very important ability and must be possessed by students in learning mathematics. Mathematical communication plays a role in understanding mathematical ideas correctly. The problem of the low mathematical communication ability of class XI IPA students at SMA Negeri 6 Skouw Kota Jayapura indicates that something is wrong in the process of learning mathematics. The low students' mathematical communication can be tried to be improved and developed by applying the articulation learning model. This research approach is quantitative with this type of experimental research with a pretest-posttest control group design. The population in this study were students of class XI IPA SMA Negeri 6 Skouw Kota Jayapura, totaling 40 people divided into 2 classes, namely, XI IPA 1 totaling 20 people, XI IPA 2 totaling 20 people. The sampling technique is total sampling. Data collection technique is a test. The type of instrument is a written test in the form of an essay. Data analysis techniques are descriptive statistics and inferential statistics (requirement test (test for normality using the Lilliefors analysis method and homogeneity test using the Fisher analysis method and hypothesis testing using the normalized gain analysis method (n-gain) and independent sample t test). Testing the hypothesis using a two-party test with the independent sample t test analysis method shows that H0 is rejected and H1 is accepted, meaning that there is an influence of the articulation learning model on the mathematical communication skills of class XI IPA students at SMA Negeri 6 Skouw Jayapura City.